Comparison of Frequency of Burst Abdomen in Diabetic and Nondiabetic Women - Seerat e Zehra, (Indus Journal of Bioscience Research, 2025)
Background: Burst abdomen, or postoperative wound dehiscence, is a serious complication of abdominal surgeries, particularly cesarean sections. Objective: To compare the frequency of burst abdomen in diabetic and nondiabetic women after cesarean section and assess the associated risk. Methods: This cohort study was conducted in the Department of Obstetrics and Gynecology at Shaikh Zaid Women Hospital, Larkana from Nov 2024 to March 2025. A total of 220 women aged 18–40 years undergoing cesarean section at ≥37 weeks gestation was included, with 110 diabetics and 110 nondiabetics. Data on demographic variables, intraoperative findings, and postoperative wound status were collected. Results: The overall frequency of burst abdomen was 7.3%. Among diabetic women, 10.9% developed burst abdomen compared to 3.6% in nondiabetics (p = 0.042). The relative risk was 3.03 (95% CI: 1.00–9.13), indicating that diabetic women were three times more likely to develop burst abdomen. Higher risk was also observed in patients with BMI ≥28 kg/m², emergency cesarean sections, and operative time ≥60 minutes. Conclusion: It is concluded that diabetic women are at significantly higher risk of developing burst abdomen following cesarean section. Early identification, preoperative risk assessment, and optimal perioperative glycemic control are critical to improving surgical outcomes in this high-risk population.